Fire use, peatland transformation and local livelihoods: a case of positive reinforcement - Chokkalingam, U.; Tacconi, L.; Ruchiat, Y. (Agency for the Assessment and Application of Technology (BPPT) and Indonesian Peat Association (IPA), 2002)
A case study from the central extensive peatland sections of the Middle Mahakam Area, East Kalimantan, is used to depic how local use of fire for agriculture extraction activities could be a major factor driving peatland transformation. Large-scale fires that occured in the area in 1982/83 and 1997/98, have resulted in transformation of some of the forested peatlands to open grass and water patches. Many of these degraded areas continue to be subject to annual, largerly uncontrolled, burning in the dry season for fish extraction. Conversion of the forested lanscape to open grass and water areas, and ultimately to lakes with repeated burning may actually enhance fishing conditions and benefit local communities, at least in the short run. The potential long-term impacts of repeated fires and landscape transformation on the vegetation, hydrological conditions, fisheries, and local livelihoods need further investigation. The scope for harmonisation of potentially divergent local interest and activities, and non-local biodiversity conservation and climate stabilisation interest in this tropical peatland ecosystem are discussed.